Embracing Co-Design: A Case Study Examining How Community Partners Became Co-Creators - Liam Murdock; Libby (Elizabeth); Luke McCarvill (MDPI AG, 2023)
Co-design increases the number of voices in a design project, which enhances the experience for all co-creators and produces a better product. A case study is presented of a ten-month co-design project-based learning experience between two engineering design students and two community partners during a first-year engineering design course, which resulted in the implementation of the device across campus. This paper evaluates the elements of co-design in the design process that was employed, documents the design product that was produced, and examines the experience of the community partners through a qualitative study. Through a retrospective examination of artifacts and files, the design process demonstrated an increase in the amount of collaboration between co-creators as the project progressed and identified 15 iterations of the design. Comparing the experience of community partners throughout the design process, five themes emerged from the semi-structured interviews: (1) emotional effects, (2) physical and mental effects, (3) productivity, (4) safety, and (5) job satisfaction. Documenting the experience of community partners throughout the design project can encourage educators to adopt co-design practices in project-based learning.